Can quantitative MRI be used in the clinical setting to quantify the impact of intra-articular glucocorticoid injection on synovial disease activity in juvenile idiopathic arthritis? - Joshua L. Bennett (Pediatric Rheumatology Online Journal, 2019)
Abstract Background Juvenile idiopathic arthritis (JIA), the most common chronic rheumatic disease of childhood, is characterised by synovitis. Clinical assessments of synovitis are imperfect, relying on composite and indirect measures of disease activity including clinician-reported measures, patient-reported measures and blood markers. Contrast-enhanced MRI is a more sensitive synovitis assessment technique but clinical utility is currently limited by availability and inter-observer variation. Improved quantitative MRI techniques may enable future development of more stringent MRI-defined remission criteria. The objective of this study was to determine the utility and feasibility of quantitative MRI measurement of synovial volume and vascularity in JIA before and twelve weeks after intra-articular glucocorticoid injection (IAGI) of the knee and to assess the acceptability of MRI to participating families. Methods Children and young people with JIA and a new episode of knee synovitis requiring IAGI were recruited from the Great North Children’s Hospital in Newcastle upon Tyne. Quantitative contrast-enhanced MRI was performed prior to and twelve weeks after IAGI, in addition to standard clinical assessment tools, including the three-variable clinical juvenile arthritis disease activity score (cJADAS) and active joint count. Results Eleven young people (5 male, median age 13 years, range 7–16) with JIA knee flare were recruited and 10 completed follow-up assessment. Following IAGI, the median (interquartile range) cJADAS improved from 8.5 (2.7) to 1.6 (3.9), whilst the median synovial volume improved from 38.5cm3 (82.1cm3) to 0.0cm3 (0.2cm3). Six patients presented with frank synovitis outside normal limits on routine MRI reporting. A further three had baseline MRI reports within normal limits but the quantitative measurements identified measurable synovial uptake. Post-IAGI quantitative measurements highlighted significant improvements in 9 patients. Conclusions IAGI led to a marked reduction in synovial volume, with quantitative MRI identifying more patients with an improved synovial volume than routine qualitative clinical reporting. Improvements in cJADAS scores were more variable with the patient/parent global assessment component contributing most to the scores. Further work is indicated, exploring the utility of quantitative MRI in the assessment of less accessible joints and comparing the impact of different treatment modalities.